Based on single very type current type sun energy and the analysis research of net inverter. Issue 6 (March 2019) - She, Minghui; Yang, Adi; Chen, Huihuang; Yu, Lun
Abstract: Article have summarized application sun energy in regenerative energy generate electricity the related content of systematic importance. On this foundation, have led into single very type three-phase current type sun energy and net inverter systematic model. With the sampling sequence theoretical and fast Fourier of frequency domain, it is the regular method that describes control strategy specificly to alternate technology with I interval ( 0 ～ 1/3 π ), for in I interval 7 alternate mould form in, analyse single very type current type sun energy specificly and net inverter system the realization of control method have gone on analyse comparatively in detail. The analog result of computer has shown the consistency of emulation and theory.